2002
DOI: 10.1248/bpb.25.1604
|View full text |Cite
|
Sign up to set email alerts
|

MDR1-Mediated Interaction of Digoxin with Antiarrhythmic or Antianginal Drugs.

Abstract: Digoxin, a cardiac glycoside, is mainly prescribed for patients with congestive heart failure. Cardiac arrhythmia sometimes occurs in patients who are taking digoxin, 1,2) and thus antiarrhythmic drugs were often co-administrated with digoxin. In fact, antiarrhythmic or antianginal drugs were also prescribed for 25% and 21% of patients taking digoxin, respectively, in our hospital.3) Digoxin is well known to have only a narrow therapeutic concentration range (trough: 0.5-2.0 ng/ml), and to be prone to drug-dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Fromm et al (1999) have shown that 5 M quinidine effectively inhibits P-gp-mediated transport of digoxin by approximately 57% in the Caco-2 MDR1-transfected cell line. Kakumoto et al (2002) also demonstrated that quinidine inhibits the transport of digoxin in MDR1-overexpressing LLC-GA5-COL150 cells with an estimated IC 50 value of 9.52 M. Here, we tested whether coperfusion of quinidine in isolated perfused rat livers could inhibit the P-gp-mediated transport of digoxin. In the liver, absorbed compounds enter the hepatocytes from the sinusoidal blood and then the drugs are either biotransformed, transported/diffused back into blood, or eliminated via biliary secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Fromm et al (1999) have shown that 5 M quinidine effectively inhibits P-gp-mediated transport of digoxin by approximately 57% in the Caco-2 MDR1-transfected cell line. Kakumoto et al (2002) also demonstrated that quinidine inhibits the transport of digoxin in MDR1-overexpressing LLC-GA5-COL150 cells with an estimated IC 50 value of 9.52 M. Here, we tested whether coperfusion of quinidine in isolated perfused rat livers could inhibit the P-gp-mediated transport of digoxin. In the liver, absorbed compounds enter the hepatocytes from the sinusoidal blood and then the drugs are either biotransformed, transported/diffused back into blood, or eliminated via biliary secretion.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the activities of CYP3A4 and P-glycoprotein contribute to the bioavailability of drugs, and the bioavailability of amiodarone is low. On the other hand, desethylamiodarone inhibits the activities of both CYP3A4 and P-glycoprotein 7,23) thus it is suggested that the bioavailability of amiodarone is gradually increased with time in subjects receiving long-term amiodarone therapy, and individual variation of the clearance decreases in subjects receiving long-term amiodarone therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The likely cause is the inhibition of P-glycoprotein activity by amiodarone [34]. During the use of amiodarone, the dose of digoxin should be reduced by 30-50% [35].…”
Section: Digoxinmentioning
confidence: 99%